The Role of Japan-ASEAN Integration Fund in Advancing Equality for Human Security and Sustainable Development - Wulandari, Diah Ayu (Indonesian Journal of Economics, Social, and Humanities, 2025)
In Southeast Asia, inequality remains a persistent problem, as differences in access to education, healthcare, technology, and economic opportunities disrupt long-term growth and regional stability. One significant collaboration to address the issue is the Japan-ASEAN Integration Fund (JAIF), which was formed to strengthen ASEAN integration efforts and promote equitable development among its member countries. This research aims to analyze the role of JAIF in advancing equalities to achieve human security and Sustainable Development. Multiple data and information related to this research are described qualitatively and analyzed using the theoretical framework of human security and sustainable development. The research findings indicate the significance of JAIF in enhancing human security within ASEAN by employing the principles of freedom from fear, freedom from want, and freedom to live with dignity. JAIF-funded activities have supported initiatives in socioeconomic empowerment, security, and capacity building in ASEAN countries. The effectiveness of JAIF is influenced by the regional political structure, economic disparities, and institutional limitations. To enhance its effectiveness, stronger collaboration between ASEAN institutions and national governments is needed to make JAIF-funded programs more adaptive and inclusive.